2016
DOI: 10.1155/2016/7576942
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Treatment on Shear Bond Strength between Resin Cement and Ce-TZP/Al2O3

Abstract: Purpose. Although several studies evaluating the mechanical properties of Ce-TZP/Al2O3 have been published, to date, no study has been published investigating the bonding protocol between Ce-TZP/Al2O3 and resin cement. The aim of this study was to evaluate the shear bond strength to air-abraded Ce-TZP/Al2O3 when primers and two different cement types were used. Materials and Methods. Two types of zirconia (Y-TZP and Ce-TZP/Al2O3) specimens were further divided into four subgroups according to primer applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 39 publications
2
9
0
1
Order By: Relevance
“…Surface treatment without air abrasion (50-µm particles) improved bond strength, regardless of whether the zirconia under went primer pretreatment. These results are consistent with those of previous studies (11,28). Treatment with air abrasion enhances surface roughness and increases surface energy, which in turn promotes resin cement flow into micro-retentions.…”
Section: Discussionsupporting
confidence: 94%
“…Surface treatment without air abrasion (50-µm particles) improved bond strength, regardless of whether the zirconia under went primer pretreatment. These results are consistent with those of previous studies (11,28). Treatment with air abrasion enhances surface roughness and increases surface energy, which in turn promotes resin cement flow into micro-retentions.…”
Section: Discussionsupporting
confidence: 94%
“…It was associated with RelyX U200, as it has a moisture tolerance structure and complete polymerization of the chemically cured part during thermocycling (37). Similar to our study, Zorzin et al (38) found that the μTBS value of Maxcem Elite increased after thermal cycling.…”
Section: Discussionsupporting
confidence: 87%
“…Metal-ceramic restorations are among the most commonly used treatment options in fixed partial dentures but have several disadvantages, such as discoloration due to the metal frame showing at the gingival margin, an opaque shade unlike natural teeth and possible metal allergy, which deems them unacceptable for both clinicians and patients 1) . Particularly, the high demand for esthetics in recent years has led to the development of all-ceramic restorations 2) .…”
Section: Introductionmentioning
confidence: 99%